12-Metal 36-membered ring based WV–CoII layers showing spin-glass behavior1. Issue 28 (28th July 2015) - Zhao, Liang; Duan, Ran; Zhuang, Peng-Fei; Zheng, Hui; Jiao, Cheng-Qi; Wang, Jun-Li; He, Cheng; Liu, Tao
<x xml:space="preserve">Abstract</x> Two cyano-bridged bimetallic WV–CoII layers were synthesized, which contain 12 metal 36 membered rings and present spin-glass behavior.